The Relationship between Mining-Induced Stress and Coal Gas under an Optimized Support Scheme: A Case Study in the Guanyinshan Coal Mine, China. (10th August 2021) - Zhang, Tianjun; Wu, Jiaokun; Chen, Yong; Ding, Hong; Ma, Hongyu; Feng, Renjun
Abstract : Stress is one of the main factors influencing coal and gas outbursts. The apparent effects of the crustal stress, the structural stress, and the mining-induced stress increase as the depth of mining increases. At present, there have been few studies of the relationship between the comprehensive analyses of the crustal stress, mining-induced stress, and coal gas. The in situ measurement of the relationship between stress-related behaviors and coal gas under the influence of mining was conducted through experimental analysis of surrounding rock support and coal and gas outburst control and optimization of surrounding rock support materials and system construction. The results showed that the mining-induced stress first increased to a peak value, then gradually decreased, and tended to stabilize as the footage progresses. Stress appears at 96 m ahead due to mining; after 57 m of advancing, there is a large increase until it passes through this area. The stress in front of the working face increases linearly, and the increase range is obviously larger than that of the coal body in a certain range on both sides. The support anchoring force gradually decreased and tended to be stable after rapidly increasing to a maximum value. The deep displacement of the roof increased linearly and tended to be stable after reaching an accumulated displacement which can reach 16-28 mm. The residual gas pressure in front of mining operations decreased rapidly, and beyond 15 m on each side of the roadway, it decreased significantly. The residual gas pressure and gas content were consistent with the gas desorption index of drill cuttings due to the influences of gas predrainage and mining. The stress along the direction of the roadway and the residual gas content, the residual gas pressure, and the gas desorption index of drill cuttings conform to the logarithmic functional relationship. The research results provide a basis for the comprehensive prevention and control of coal and gas outbursts from multiple angles considering stress, coal, and gas.